Effect of Soaking and Non-soaking Condition on Shear Strength Parameters of Sandy Soil Treated with Additives - Roaa M. Fadhil; Haifaa A. Ali (Civil Engineering Journal, 2019)
The present paper aims to improve shear strength parameters: cohesion (c), and angle of internal friction (∅) for sandy soil treated by additives before and after soaking. The samples of sandy soil were obtained from Karbala city and then classified as poorly graded sand (SP) with relative density Dr (30%) according to the system of (USCS). The experiment has three stages. In the first stage ,the soil was treated with three different  percentages of cement (3 ,5 and 7%) of dry weight for the soil with three different percentages of water content (2, 4 and 8%) in each above percentage of cement, while the second stage includes (2%) of lime  from  soil weight  mixed with each different percentage of cement . In the third stage, (50%) of polymer of cement weight was mixed with each different percentage of cement. An analysis of behavior sandy soils treated by additives was carried out with the Direct Shear Tests. All the samples were cured (3) days before and after soaking. The results of the experiment showed that increase in shear strength parameters of sandy soil; especially the angle of internal friction with the rate value (16.6 %) of cement only, (21.88 %) of cement with lime , (20.3%) of cement with the polymer before soaked condition. After soaking condition, it was increased with the rate value (14.3%) with cement only, (23.57%) of cement with lime, and (15.38%) of cement with the polymer as compared with soil in the natural state.